Методичні аспекти визначення ефективності виробництва зерна в сучасних умовах - Lositska, Tetyana (Dr. Viktor Koval, 2019)
Introduction. The pace of development of the agro-food market of Ukraine is extremely volatile, due to the determinants of the external environment and internal factors. In the context of accelerated integration processes, the potential of free trade areas and regional trade associations have an impact on the structure of the internal market as a whole and the agro-food market in particular. Given the leading position of the agro-food sector in the national economy and the significant share of grain exports in total exports of Ukraine, the problem of ensuring the efficiency of grain production is of particular relevance for the domestic economy. Aim and tasks. The purpose of this paper is is to systematize the methodological bases for determining the efficiency of grain production in modern conditions. According to the stated purpose, the main objectives of the study are: to generalize the instrument of production efficiency estimation in the market of agro-food products and to identificate the determinants of influence on efficiency of grain production in the conditions of increasing openness of national economies. Results. The results of the study of theoretical foundations of problems of ensuring the efficiency of agricultural production from the standpoint of economic and socio-economic approach made it possible to identify the determinants of increasing the efficiency of grain farming in the context of natural and climatic conditions, biological and organizational and technological features of its production. Based on the generalization of indicators of economic efficiency of placement and specialization of grain production, it is determined that the efficiency of grain production can be calculated on the basis of indicators in the context of quantitative and qualitative indicators. Conclusions. Given the prospect of maintaining its strategic importance not only in agriculture, but in the Ukrainian economy as a whole, grain will continue to remain dominant in the development of the agro-industrial complex, both in terms of the need to provide food security and in view of the potential for increasing export potential in Ukraine in this area. Forecasts of future world trade trends by major agricultural commodities are favorable for Ukraine in the medium term, given the potential of domestic grain exports. Prospects for further study of this issue are to identify the ways of strengthening the export orientation of Ukrainian enterprises in the grain market.